Inhibition of ABL1 tyrosine kinase reduces HTLV-1 proviral loads in peripheral blood mononuclear cells from patients with HTLV-1-associated myelopathy/tropical spastic paraparesis - Kodama, Daisuke (PLoS Negl Trop Dis, 2020)
Human T-cell leukemia virus type 1 (HTLV-1) causes incurable adult T-cell leukemia and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). Patients with HAM/TSP have increased levels of HTLV-1-infected cells compared with asymptomatic HTLV-1 carriers. However, the roles of cellular genes in HTLV-1-infected CD4+ T cells await discovery. We performed microarray analysis of CD4+ T cells from HAM/TSP patients and found that the ABL1 is an important gene in HAM/TSP. ABL1 is a known survival factor for T- and B-lymphocytes and is part of the fused gene (BCR-ABL) known to be responsible for chronic myelogenous leukemia (CML). ABL1 tyrosine kinase inhibitors (TKIs), including imatinib, nilotinib, and dasatinib, are used clinically for treating CML. To evaluate whether ABL1 is indeed important for HAM/TSP, we investigated the effect of TKIs on HTLV-1-infected cells. We developed a propidium monoazide-HTLV-1 viability quantitative PCR assay, which distinguishes DNA from live cells and dead cells. Using this method, we were able to measure the HTLV-1 proviral load (PVL) in live cells alone when peripheral blood mononuclear cells (PBMCs) from HAM/TSP cases were treated with TKIs. Treating the PBMCs with nilotinib or dasatinib induced significant reductions in PVL (21.0% and 17.5%, respectively) in live cells. Furthermore, ABL1 siRNA transfection reduced cell viability in HTLV-1-infected cell lines, but not in uninfected cell lines. A retrospective survey based on our clinical records found a rare case of HAM/TSP who also suffered from CML. The patient showed an 84.2% PVL reduction after CML treatment with imatinib. We conclude that inhibiting the ABL1 tyrosine kinase specifically reduced the PVL in PBMCs from patients with HAM/TSP, suggesting that ABL1 is an important gene for the survival of HTLV-1-infected cells and that TKIs may be potential therapeutic agents for HAM/TSP.